1998
DOI: 10.1007/bf02550224
|View full text |Cite
|
Sign up to set email alerts
|

Early repair of injury to the ureter or bladder after hysterectomy

Abstract: In the present study we investigated the effectiveness of early diagnosis, repair of injuries to the ureter and urinary bladder sustained during hysterectomy, as compared to the results of delayed intervention. There were 46 ureteral injuries and 20 vesicovaginal fistulas in 55 patients. In 14 cases of ureteral injury an endoscopic approach management was employed. There was complete healing in 18 vesicovaginal fistulas while there was a single case of a ureteral injury that required nephrectomy because of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…Hysterectomy, both by transabdominal and transvaginal approaches, is the most common procedure, comprising 75% of iatrogenic fistulae 10 . Globally, the overall incidence varies between 0.5 and 1.5%, and bladder injuries are more common than ureteric ones 14 . In pelvic surgery the development risk of VVF is 0.22% in laparoscopic hysterectomy, 0.1% in abdominal hysterectomy and 0.02% in vaginal hysterectomy 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hysterectomy, both by transabdominal and transvaginal approaches, is the most common procedure, comprising 75% of iatrogenic fistulae 10 . Globally, the overall incidence varies between 0.5 and 1.5%, and bladder injuries are more common than ureteric ones 14 . In pelvic surgery the development risk of VVF is 0.22% in laparoscopic hysterectomy, 0.1% in abdominal hysterectomy and 0.02% in vaginal hysterectomy 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This socio-demographic scenario is almost identical to other study in developing countries 7,13 . One study in Turkey reported the mean patient age as 43(±SD 3.86) years 14 . The alarming part is that majority of the cases occurred in middle age group and if not treated these women would have to spend a long part of their lives with this affliction, creating social and psychological problems in addition to medical issues.…”
Section: Discussionmentioning
confidence: 99%
“…Nossos resultados demonstraram incidência semelhante. As injúrias do ureter e bexiga durante a histerectomia devem ser tratadas imediatamente no intra-operatório, pois requerem técnicas cirúrgicas mais simples e evitam maior trauma para a paciente 13 .…”
Section: Discussionunclassified
“…Surgical management of unrecognized ureteric injuries is more complex in comparison to repair at the time of injury (11). The traditional recommendation of delaying repair by several months to allow edema to subside, tissue plane to be re-established, and fistula to become small prior to attempted repair (14) has been debated with some urological surgeons now advocating immediate repair (7,15,16). Percutaneous (17)(18)(19) and endoscopic (14,20) approaches offer alternative treatment options with good reported outcomes.…”
Section: Introductionmentioning
confidence: 99%